Challenges in cardiovascular pharmacogenomics implementation: a viewpoint from the European Society of Cardiology Working Group on Cardiovascular Pharmacotherapy. Issue 1 (31st August 2021) - Magavern, Emma F; Kaski, Juan Carlos; Turner, Richard M; Drexel, Heinz; Janmohamed, Azara; Scourfield, Andrew; Burrage, Daniel; Floyd, Christopher N; Adeyeye, Elizabeth; Tamargo, Juan; Lewis, Basil S; Kjeldsen, Keld Per; et al.
Abstract: Pharmacogenomics promises to advance cardiovascular therapy, but there remain pragmatic barriers to implementation. These are particularly important to explore within Europe, as there are differences in the populations, availability of resources, and expertise, as well as in ethico-legal frameworks. Differences in healthcare delivery across Europe present a challenge, but also opportunities to collaborate on pharmacogenomics implementation. Clinical workforce upskilling is already in progress but will require substantial input. Digital infrastructure and clinical support tools are likely to prove crucial. It is important that widespread implementation serves to narrow rather than widen any existing gaps in health equality between populations. This viewpoint supplements the working group position paper on cardiovascular pharmacogenomics to address these important themes.